TANGGUNG JAWAB PELAKU USAHA FITNESS TERHADAP KONSUMEN PENGGUNA SUPLEMEN FITNESS YANG TIDAK MEMILIKI IZIN EDAR DI KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The government in the effort to protect consumers has a very important role as an intermediary between the interests of business actors and the interests of consumers, /with that the government makes a rule that protects the interests of consumers. The regulation is Law Number 8 of 1999 Concerning Consumer Protection or often abbreviated as UUPK. The Consumer Protection Act consists of 15 chapters and 65 articles which regulate consumer protection where there are guarantees for consumer rights. This law is effective since it was passed precisely on April 20, 2000.This research is an empirical or sociological legal research by means of a research survey that takes a sample from one population and uses a questionnaire as the main data collection. While the population is a whole or a collection of objects with the same characteristics. population can be a set of people, objects (living or dead), events, cases, times, or places with the same characteristics or characteristics. The sample is a number of people or entities that are part of the population that will be used as a data source.From the results of the research that the author did can be concluded, first Based on Law No. 8 of 1999 concerning Consumer Protection, business actors should be responsible for providing compensation or compensation for the loss of fitness supplement consumers without marketing authorization that is traded by fitness business practitioners. Second, the author considers that the efforts made by consumers against fitness businesses are completely absent due to lack of information on how efforts should be taken by consumers if consumers feel disadvantaged because they have consumed fitness supplements that do not have marketing authorization.Keywords: Responsibility - Fitness Business - Consumer Fitness Supplements